The Role of Universities in Pioneering Halal Product Innovation and Education in Indonesia - Handi Risza (STAI Hubbulwathan Duri, 2024)
As the global halal market continues to expand, the role of educational institutions in fostering sector growth becomes increasingly crucial. This systematic literature review investigates the role of Indonesian universities in driving halal product innovation and education, which is essential in a country with the largest Muslim demographic worldwide. The review synthesizes findings from diverse scholarly articles, including peer-reviewed journals and government reports, published between 2015 and 2023, to present a comprehensive overview of how higher education institutions contribute to the halal sector's growth. It focuses on areas such as curriculum development, research initiatives, industry-academia collaboration, and the impact of these activities on the halal market. The methodology includes a rigorous selection process, adhering to predefined inclusion and exclusion criteria, and leveraging databases such as Google Scholar, PubMed, and governmental archives, ensuring the analysis's relevance and depth. Key themes emerge, such as the integration of halal standards in academic programs, the role of universities in halal certification processes, and the incubation of halal product startups within university environments. The review also identifies gaps in existing research, notably in the quantification of universities' contributions to the halal market and the long-term outcomes of halal-focused education. Finally, the paper suggests areas for future research, including the need for longitudinal studies to assess the sustained impact of higher education on the halal industry's evolution in Indonesia and globally. This review provides policymakers with a framework for supporting academic programs that align with industry needs, thereby enhancing the national economy in Indonesia. It also offers valuable insights for academics and industry practitioners aiming to leverage educational institutions to foster innovation in the halal product sector.